What Kind of 'Knowledge' is English? (Re-reading the Newbolt Report). Issue 3 (3rd July 2017) - Doecke, Brenton
Abstract: This essay takes Michael Young's 2007 call 'to bring knowledge back in' as an occasion to reflect on the relationship between subject English and the disciplinary knowledge that provides its foundations. It focuses on a key text in the history of English teaching, namely The Teaching of English in England, published in 1921 (otherwise known as the Newbolt Report), arguing that it reflects a moment in the emergence of English as a cultural praxis that is still relevant to us, especially with respect to the claims it makes for literature as the core of subject English. The richness of subject English as it is embodied in its history cannot be comprehended by Young's understanding of 'knowledge'.